(untitled) (GEON Journal (Management, Organizations and Business), 2017)
The intention of the research go to analyze the strategic addressing of small factories of the clúster of Wood in the department of Atlantic, which make face to a big challenges of growth and sustainability depending on the environment where they are developed. It was base don a methodological qualitative approach, with a type of explanatory, essential research for the explanation of the studied variables an its conditions. Additional to this, the research is carried out across a study of cases, the population was shaped by the micromanifacturing plants of furniture, and the key informants were 8 of then, which were selected in an intentional way. As tool of analyssi was ued the MMGO model. The results indicated that the manufacturing processes of furniture execute of form Semi Industrial added to this, the inadequate managing of resources, lack of planning, classification and a low joint of the process, carries to present a low competitiveness. Likewise, the implementation of a plan to standardized in the processes orientated to the improvement of the quality of the products. The significant weaknesses are demonstrated in its strategic processes, organizacional structure ande human management, however, they have managed to support on a competitive and dynamic market, as is the furnitur and Wood sector across the tolos that the strategic addressing offers, there was demonstrated that the companies for very small that are they can develop organizational practices that allow to arrange its business functions to face the market demands.